Save now or die trying : - Bruno, Mark (J. Wiley & Sons Inc., 2007)
Written in a straightforward and accessible style, this guide will show you how to take full advantage of the most important elements of the retirement planning process--time and participation. Through practical profiles of young adults dealing with difficult financial situations and detailed discussions with scores of financial advisors about the various options available for building long-term wealth--from IRAs to 401(k)s--you'll quickly learn how to overcome the challenges of successfully saving for retirement.